POSTPARTUM PSYCHIATRIC DISORDERS - A NEGLECTED AREA IN PAKISTAN - Yousafzai, Abdul Wahab; Shezah Khalid (Journal of Ayub Medical College Abbottabad, 2024)
Postpartum psychiatric disorders, from mild Postpartum Blues to severe Depression and Psychosis, represent an underrepresented crisis in Pakistan. Despite their impact on maternal and neonatal health, these conditions are often misdiagnosed and untreated. Contributing factors include weak familial support, sociocultural stigma, and lack of awareness, especially in underserved areas. The negligence towards new mothers highlights the gaps in maternal mental health care in Pakistan, where regulatory frameworks are still evolving. This editorial explores the crisis, critiques existing services, and provides recommendations to improve early identification and intervention, aiming to raise awareness and provide strong support for affected mothers.